Relationship of leptin with insulin indices in gestational diabetes mellitus (Journal of Association of Clinical Endocrinologist and Diabetologist of Bangladesh, 2025)
Background: Leptin is thought to increase and affect glucose and insulin homeostasis in gestational diabetes mellitus (GDM).Objectives: To see the relationships among leptin, insulin indices (homeostatic model of insulin assessment, HOMA-IR), and obesity among women with GDM.Methods: Women (n=107) with 24-28 weeks gestation were tested by 75 gm oral glucose (OGTT) to divide into GDM [n=45, age: 27.80±3.98 years, mean±SD; BMI: 27.88(24.46, 30.43) kg/m2, median] and normal glucose tolerance [NGT; n=62, age: 26.19±5.30 years, mean±SD; BMI: 25.80(23.65,28.42) kg/m2, median] following WHO-2013 diagnostic criteria. Fasting plasma glucose, insulin, and leptin were measured by glucose oxidase and ELISA methods respectively.Results: Glucose values (fasting, 01h, and 02h; mmol/L) were significantly higher in GDM than those of NGT in both subgroups of HOMA-IR [≥2.89: insulin resistant (IR),